Synthesis and Characterization of a New Semiconductor Oligomer Having Quinoline and Fluorene Units - Correia,Fábio C. (2015)
A new oligomer having fluorenylene and quinolinylene groups was straightforwardly synthesized by Suzuki reaction and proven to be readily soluble in common organic solvents. The chemical structure of the copolymer was confirmed and characterized by 1H nuclear magnetic resonance (NMR), Fourier transform infrared (FTIR), differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and gel permeation chromatography (GPC) measurements. In solution, the oligomer presented two absorption maxima at 314 and 245 nm, along with a high fluorescence quantum yield (82%), characterized by an emission maximum at 419 nm. The band gap of the material was estimated to be around 2.60 eV by cyclic voltammetry, however the optical band gap for the thin film observed by UV-Vis spectroscopy was 3.10 eV. The divergence was attributed to charge transfer interactions due to the presence of donor and acceptor units in the copolymer.